Позднесарматское погребение в Центральном Крыму - Мульд, С.А. (Материалы по археологии, истории и этнографии Таврии, 2001)
В фондах Крымского Республиканского краеведческого музея более десяти лет хранится археологический комплекс позднесарматского времени. Кроме экспедиционных шифров на упаковках вещей, другой сопровождающей его документации нет. Известно, что предметы были сданы в музей сотрудником Крымского филиала Института археологии АН УССР К.К.Орловым. In 1989 in the outskirts of the village Michurinskoe in the Central Crimea a vault of the late Sarmatian period was examined. Orlov K.K., a supervisor of the excavation, moved away from scientific activity and did not give a report about this work. All the things were transposed to the Crimean Republican Museum of Local Lore, History and Economy. Testimony of the participants of the expedition enabled us to place some details of the burial. In the subsoil vault of T-shaped planning there was a female burial. The costume of a dead woman was decorated with a large quantity of sewn beads and gold plates. Bracelets, finger rings and earrings were used as ornaments. Besides, an amphora, incense burner, iron details of a casket, bridle set were found in this vault. The latter one is of a particular interest, because similar sets are characteristic detail of rich Sarmatian war complexes revealed in the steppe districts from the Southern Urals district to the estuary of the Danube. Several “riders’" burials are known and in the Crimea. For the first time a bridle set was found in the female’s burial. The burial is dated back to the first half of the 3rd century AD. The whole complex testifies to a high social position of the buried woman.